Some Methods to Estimate the Parameters of IDAL-Distribution (b) - M. Hamad, Alaa; H. Alkanani, Iden (Al-Nahrain Journal of Science, 2025)
This paper estimates three parameters for a new model called “IDAL Distribution”. This model expands the exponential Weibull distribution by adding a third parameter and studying its characteristics. Several estimation methods, such as maximum likelihood estimation, ordinary least squares estimation, and proposed ordinary least squares methods, have been used to investigate the unknown parameters of the IDAL distribution. The goodness of fit of the proposed distribution is ultimately compared, and the results of the applied approaches are evaluated based on MSE.